Virtual Public Sphere On Social Media (Habermas' Critical Study Of The Digital Hoax Phenomenon Whatsaap Group Alumni Iluni Menwa UI) - Dinar Soelistyowati, Rr; Subhan, Arief; Rinanto Sigit, Ridzki (CV. Inara, 2024)
The present study aims to examine the phenomenon of the Virtual Public Sphere on social media, specifically focusing on the impact of digital hoaxes within the ILUNI Menwa UI Alumni WhatsApp Group. In the contemporary era of digital information, the proliferation of digital hoaxes, particularly those about the COVID-19 pandemic, has emerged as a noteworthy concern, exerting a discernible influence on public discourse. The primary objective of this study is to examine the effects of digital hoaxes on the Virtual Public Sphere. This research addresses a significant vacuum in the existing literature by integrating three critical theoretical frameworks: New Media Theory, Network Wealth Theory, and Jürgen Habermas' Concept of Virtual Public Spheres. The research inquiry examines the influence of digital hoaxes on communication and social interaction within the Virtual Public Sphere on WhatsApp and their potential ramifications on social integration within virtual groups. The existing body of research exhibits a notable deficiency in comprehending the significance of WhatsApp as a widely utilised social media platform within social communication, particularly regarding the potential risks associated with disseminating digital hoaxes. The research employed a qualitative methodology, specifically in-depth interviews with 30 ILUNI Menwa UI Alumni WhatsApp Group participants. In addition, a content analysis was conducted on the messages inside the group to gain insight into the impact of digital hoaxes on communication dynamics. The study's results indicate that digital hoaxes can impede logical discourse, generate disputes in information, and potentially undermine the integrity of communication on the WhatsApp platform. This study offers a comprehensive analysis of the function of social media, specifically WhatsApp, in forming a Virtual Public Sphere. It also examines the potential consequences of digital hoaxes on social integration within virtual communities during the COVID-19 epidemic.